Tiny Space Architecture: A Dialectical Inquiry into Scale, Scarcity, and Spatial Ethics - Wiratama, Army; Ikaputra (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2026)
Rapid urban densification, environmental constraints, and socio-economic pressures have intensified interest in compact living environments. Although research on tiny houses and small dwellings has expanded, existing studies remain fragmented, emphasizing technical performance, sustainability, or lifestyle motivations without providing a coherent theoretical foundation for spatial smallness. This study develops Tiny Space Architecture (TSA) as a theoretical framework that reconceptualizes spatial limitation as a generative and ethical architectural condition. Using a dialectical-critical approach, it systematically reviews and interprets philosophical and architectural literature published between 1800 and 2025 through conceptual mapping, comparative analysis, and theoretical synthesis. The findings identify three architectural registers of tiny space and formulate five core concepts: spatial compression, spatial fluidity, architecture as control, conditions of scarcity, and recalibration of relief. Integrated through ontological, epistemological, and axiological dimensions, these concepts define TSA. The study positions spatial limitation as a productive rather than deficient design condition, providing a theoretical foundation for future research on compact living, sustainability, and spatial justice.